Research: Beyond promotions, indexing agencies and impact factors! - J.V. Dixit (Al Ameen Medical College, 2022)
Many researchers are tempted to publish their research in supposedly "predator" journals. It is definitely not their first choice! Still they do it for the very reason that somehow they want to publish their research. The question is, whether it is really possible to publish your honest research in the present scenario? In this editorial I am attempting to point out some hurdles in scientific publication and possible solutions.